Sosialisasi Penyalahgunaan Narkoba Dan Pemberian Nilai Edukasi Akan Bahaya Narkoba Di SMK Negeri 01 Woja - abdul harits17; Agussalam; Umar Sagaf; Aminullah; Muhammad Amin (Jurnal Teras Pengabdian Masyarakat, 2025)
Drug abuse is a serious threat that can damage the future of the younger generation, especially students who are in a period of development and self-discovery. This seminar was held as a form of education and prevention against drug abuse in the school environment, especially at SMK Negeri 01 Woja. The purpose of this community service activity is to provide educational value and direction to students at SMK NEGERI 01 Woja about the dangers of drug abuse for their health and future. through the Drug Seminar activity. The method used is an educational-participatory approach, namely providing education that involves the active participation of students, teachers, and related parties by holding a Drug Seminar activity in providing educational value to students. The participants in this service are all students who attend the Drug Seminar activity. This service was carried out at SMK NEGERI 01 Woja, Mumbu Village, Dompu Regency, West Nusa Tenggara on August 15, 2023 at 09.00 WITA until finished. The speakers presented several speakers consisting of BNN, Health Service, Police and also village officials. The results of this Drug seminar activity showed that through a participatory, socialization and collaborative approach through this Drug seminar, students were enthusiastic in responding to the activity, many students asked questions related to the dangers of drug abuse and its impacts. Not only students but also teachers took part in responding to the discussions presented by several speakers.